Trade Unions on YouTube Online Revitalization in Sweden - Jansson, Jenny (Springer Nature, 2019)
This open access book investigates how trade unions representing different social classes use YouTube videos for renewal purposes. Information and communication technology has undoubtedly offered new opportunities for social movements, but while research suggests that these new means of communication can be used for trade union revitalization, few studies have examined what unions actually do on social media. By analysing more than 4500 videos that have been uploaded by Swedish trade unions, Jansson and Uba explore how unions use YouTube to address issues such as recruiting new members, improving internal democracy, promoting political campaigns and constructing (new) self-images. The results demonstrate that trade unions representing a range of social classes use different revitalization strategies via YouTube. This research will be of use to students and scholars researching European politics and political participation, trade unionism and labour movements in the digital age.